Melatonin: A promising candidate for maintaining food security under the threat of phytopathogens - Gupta, R.
Plant immune response is tightly controlled by an interplay of various phytohormones and plant growth regulators. Among them, the role of salicylic acid, jasmonic acid, and ethylene is well established while some others such as nitric oxide, polyamines, and hydrogen sulfide have appeared to be key regulators of plant immunity. In addition, some other chemicals, such as melatonin (N-acetyl-5-methoxytryptamine), are apparently turning out to be the novel regulators of plant defense responses. Melatonin has shown promising results in enhancing resistance of plants to a variety of pathogens including fungi, bacteria, and viruses, however, the molecular mechanism of melatonin-mediated plant immune regulation is currently elusive. Evidence gathered so far indicates that melatonin regulates plant immunity by (1)facilitating the maintenance of ROS homeostasis, (2)interacting with other phytohormones and growth regulators, and (3)inducing the accumulation of defense molecules. Therefore, engineering crops with improved melatonin production could enhance crop productivity under stress conditions. This review extends our understanding of the multifaceted role of melatonin in the regulation of plant defense response and presents a putative pathway of melatonin functioning and its interaction with phytohormones during biotic stress.
Keywords: BIOTIC STRESS; HORMONES; MELATONIN; PLANT DEFENSE; PLANT GROWTH REGULATORS; PLANT-PATHOGEN INTERACTION; SIGNALING